2010
DOI: 10.1002/j.2055-2335.2010.tb00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot of Antimicrobial Stewardship in Australian Hospitals

Abstract: Background:The diminishing investment into the development of new antimicrobials is of significant global concern. This, coupled with the emergence of anti-infective drug resistance, highlights the need to both prolong and optimise the use of existing antimicrobials. Strategies or programs to optimise antimicrobial use fall under the broad heading of antimicrobial stewardship. Aim: To identify the types of antimicrobial stewardship programs in existence in Australian hospitals and their perceived success. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
(31 reference statements)
1
15
0
Order By: Relevance
“…Previous studies of similar interventions have found similar patterns of intervention, but on a much less intensive scale 10 . ‐ 12 Despite this, only six of 78 respondents in an Australian survey of hospital pharmacies reported implementing regular multidisciplinary antimicrobial stewardship ward rounds 13 …”
Section: Discussionmentioning
confidence: 98%
“…Previous studies of similar interventions have found similar patterns of intervention, but on a much less intensive scale 10 . ‐ 12 Despite this, only six of 78 respondents in an Australian survey of hospital pharmacies reported implementing regular multidisciplinary antimicrobial stewardship ward rounds 13 …”
Section: Discussionmentioning
confidence: 98%
“…It was a multicenter cross sectional survey with focus on one response from each representative hospital. Firstly, a web based survey adopted from Chen et al (2010a) was distributed in all Makkah hospitals and selected hospitals in Jeddah and Taif city. Only tertiary care hospitals in Taif and Jeddah region were selected under the Ministry of Health and other public health sectors for generalizability.…”
Section: Methodsmentioning
confidence: 99%
“…In Kansas, United States, Poteete et al revealed in a state-wide survey that 48% of the institutions had a multidisciplinary stewardship committee to supervise stewardship programs ( Poteete and Scaletta, 2017 ). In Australia, Chen et al reported that 80 pharmacy directors had a variety of ASP strategies with different levels of success to guide rational antimicrobial use in healthcare settings ( Chen et al, 2010a ). The most common ASP strategies were the existence of a multidisciplinary drug and therapeutic committee, formulary restriction, clinical pharmacy services, infectious disease consultation and education- and training-related activities.…”
Section: Introductionmentioning
confidence: 99%
“…13 The method involved an anonymous postal survey and qualitative interviews with stakeholders. Ethics approval was granted by the Monash University Human Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%